Adolescent loneliness and social anxiety: The role of multiple sources of support. (March 2016) - Cavanaugh, Alyson M.; Buehler, Cheryl
This study tested whether cumulative support (i.e., parental, interparental, peer, and teacher) was associated with decreases in youths' loneliness and social anxiety during early adolescence. The unique associations of support sources and moderating effects of youth gender also were examined. Participants included 416 youth in sixth grade at the beginning of the study (mean age = 11.86, SD = .69; 91% European American). Cumulative support during sixth grade was associated with decreased loneliness and social anxiety across early adolescence, and it was found that the association with decreased social anxiety was stronger for boys than girls. Parental and peer support were uniquely associated with decreased loneliness and social anxiety, respectively. The protection offered by multiple sources of support for developmental tasks across early adolescence is discussed.